USLUB IJAZ DALAM STILISTIKA AL-QUR'AN: KAJIAN STRUKTUR - Mardjoko Idris (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2020)
Each distinction has an essay and every article has a distinction, and this term is what is intended to study the science of rhetoric, i.e. conformity of speech to the requirements of the case and brevity is a type of Arab speech and has a place. The case may require brevity in saying, and then eloquence will be in that the speaker be summarized and his speech shortened. And brevity is of two types: shortening is a sign of the many meanings in a few words, and brevity by tapping it is the expression of many meanings in a few words, by deleting something from the composition without prejudice to those suffering, and brief by deleting it may be a part of a word or a word or a sentence or more than a sentence.